2015
DOI: 10.1021/acs.jpcb.5b05616
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Study on the Interactions between Carboxylate Ions and Metal Ions in Water

Abstract: The interaction between a carboxylate anion (deprotonated propanoic acid) and the divalent Mg(2+), Ca(2+), Sr(2+), Ba(2+) metal ions is studied via ab initio molecular dynamics. The main focus of the study is the selectivity of the carboxylate-metal ion interaction in aqueous solution. The interaction is modeled by explicitly accounting for the solvent molecules on a DFT level. The hydration energies of the metal ions along with their diffusion and mobility coefficients are determined and a trend correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 40 publications
(103 reference statements)
8
40
0
Order By: Relevance
“…Radial distributions (RDFs: Figure 4) of O (water) obtained from AIMD simulations for eight metal ions in water define inner-shell structures for alkali metal ions and alkaline earth metal ions. Those AIMD results are consistent with the accurate experimental determinations of peak positions (Table 1), and with alternative studies of particular cases (136,137,138). These ions are often compared to investigate effects of the ion charges and sizes on channel behavior.…”
Section: Ion Hydration Structuresupporting
confidence: 80%
“…Radial distributions (RDFs: Figure 4) of O (water) obtained from AIMD simulations for eight metal ions in water define inner-shell structures for alkali metal ions and alkaline earth metal ions. Those AIMD results are consistent with the accurate experimental determinations of peak positions (Table 1), and with alternative studies of particular cases (136,137,138). These ions are often compared to investigate effects of the ion charges and sizes on channel behavior.…”
Section: Ion Hydration Structuresupporting
confidence: 80%
“…Various CPMD 41,42,62,63 studies of the hydration structure of Ca 2+ calculated CN in the range 5.9 41 to 7.2 62 and Ca-O distances of 2.36 41 to 2.45 Å. 63 A BOMD study by Mehandzhiyski et al 64 found a CN of 7 with a Ca-O distance of 2.45 Å, in agreement with earlier CPMD studies.…”
Section: +supporting
confidence: 74%
“…71 Various computational methods have been used to evaluate the first shell solvation structure of Sr 2+ including DFT, 73 Quantum Mechanical/Molecular Mechanics (QMMM), 74 QMSTAT 58 as well as MD and AIMD. 41,64,75 A Sr CN of around 8 40,56,64,[76][77][78][79] is typically identified within a range of CNs between 6.7 41 and 9.8 47 and Sr-O distances of 2.58 40 to 2.69. 58 A recent paper by D'Angelo et al 79 combined experimental and computational techniques to investigate the coordination shell of Sr 2+ using X-ray absorption near-edge spectroscopy (XANES) of [Sr(H 2 O) 8 ](OH) 2 , MD and CPMD.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Ab initio molecular dynamics of ions in solutions can be performed, and many such studies have been reported (e.g., [48][49][50][51][52] ). Unfortunately, such simulations are limited to small systems and short periods.…”
Section: Approachmentioning
confidence: 99%